Effect of humic acid on the adsorption capability of natural clay. - Deseo, Ma. Rogemae G.
Adsorption capability and kinetic profile of natural clay are fundamental in developing innovations. Understanding the effect of humic acid in the adsorption properties of natural clay maximizes the potential use of these materials in controlled release and slow release fertilizers. In this study, the adsorption isotherm and kinetics of methylene blue, as the cationic-organic guest analogue, on natural clay and the effect of humic acid on the adsorption mechanism were studied. Natural clay was first characterized using TGA, FTIR, and Raman spectroscopy. Potentiometic titration and FTIR were done to characterize the humic acid. Experimental results were obtained by batch adsorption experiments and spectroscopic analysis of methylene blue. It showed that the rate of adsorption increases with the mass of the adsorbent. 15 min for 0.450g, 0.375g, and 0.300g of clay and 120 min for 0.225 g and 0.150g (70%). The optimal contact time and mass of adsorbent utilized for the adsorption isotherm experiment were 20 mins and 0.450g, respectively. Adsorption isotherms were generated by varying the initial concentration (50-150 ppm) of methylene blue solution. Coadsorption with humic acid was was carried out using the same concentration range. Results showed that humic acid decreases the adsorption capacity of clay form 44 mg/g to 22.8 mg/g. The experimental data showed good fitting to the Langmuir model and the hindrance due to humic acid was evidence by the decreased parameter values more importantly in the R^2 values from 0.98 to 0.97. To assess the kinetics of adsorption, equilibrium data were fitted on Pseudo-First order and Pseudo-Second order kinetic models and the resulting R^2 values obtained from the plots were 0.97 to 0.99, respectively. Thus, from the results of the kinetics of adsorption follows pseudo-second order.